2015
DOI: 10.1007/s00221-015-4452-0
|View full text |Cite
|
Sign up to set email alerts
|

Vocal response inhibition is enhanced by anodal tDCS over the right prefrontal cortex

Abstract: Stopping outright (reactive inhibition) and slowing down (proactive inhibition) are types of response inhibition which have mainly been investigated in the manual effector system. This study compared reactive inhibition across manual and vocal effector systems, examined the effects of excitatory anodal transcranial direct current stimulation (anodal tDCS) over the right prefrontal cortex (right-PFC) and looked at the relationship between reactive and proactive inhibition. We hypothesised (1) that vocal reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 59 publications
5
18
1
Order By: Relevance
“…The tDCS parameters used in the present study are consistent with those previously reported in the response inhibition literature to demonstrate increased task performance (i.e. <2 mA stimulation with an anode over the frontal cortex and a stop-signal task to measure response inhibition, [30][31][32][33]. In contrast, to our knowledge there are no published reports demonstrating impaired response inhibition via tDCS, thus supporting our a priori hypothesis.…”
Section: False Alarm Ratesupporting
confidence: 90%
See 2 more Smart Citations
“…The tDCS parameters used in the present study are consistent with those previously reported in the response inhibition literature to demonstrate increased task performance (i.e. <2 mA stimulation with an anode over the frontal cortex and a stop-signal task to measure response inhibition, [30][31][32][33]. In contrast, to our knowledge there are no published reports demonstrating impaired response inhibition via tDCS, thus supporting our a priori hypothesis.…”
Section: False Alarm Ratesupporting
confidence: 90%
“…Specifically, recent studies have demonstrated improved response inhibition following conventional tDCS with an anode placed over right IFC or presupplemetary motor area (preSMA) and the cathodal electrode placed on the opposite side of the head [30][31][32][33]. Given the well-established role of right IFC and preSMA in response inhibition [2,3], the studies" authors argued that enhanced excitability at the structures underneath the anodal pad drove the observed behavioral improvement.…”
Section: Effects Of High-definition and Conventional Tdcs On Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, tDCS can be a powerful tool to make causal inferences about the role of the regions and processes involved in SST performance. Several studies have found decreased SSRTs following anodal stimulation of the IFG [29][30][31][32][33][34] , suggesting that this method can indeed alter inhibition latencies. However, both increased and decreased reaction times in go trials have also been reported 10,31,35 , indicating that anodal IFG stimulation could potentially influence strategic adjustments of task performance rather than an inhibitory process per se.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings, transcranial direct current stimulation (tDCS) studies report that modulations of ventrolateral prefrontal cortex (VLPFC) excitability can improve inhibition performance [ 5 12 ]. Jacobson and colleagues [ 7 ] for instance report shorter stop signal reaction times (SSRT) after excitatory anodal than sham tDCS over the rIFG during a stop-signal task (SST; see also [ 10 , 11 ]; and [ 6 , 8 , 12 ] for similar results when applying anodal tDCS over the preSMA).…”
Section: Introductionmentioning
confidence: 99%